Research of renewable energy penetration rate in integrated energy stations - Qingguang Yu (Elsevier, 2021)
A multi-energy plant combines renewable energy generation equipment, a charging station and a charging station with storage. This paper discusses integrated power systems that make full use of existing substations and support the construction of data centers, energy storage, 5g base stations, photovoltaic power plants, wind farms, gas turbines, etc., to create an advanced integrated energy system that enables the integration and sharing of resources and increases energy efficiency. The simulation results confirm that the integrated power plant system plays an important role in increasing the share of renewable energy production. Self-generation and control can in principle achieve 100% solar electricity consumption, and energy storage devices play a key role in renewable energy consumption.